2008
DOI: 10.1002/elps.200700413
|View full text |Cite
|
Sign up to set email alerts
|

Determination of organic anions in atmospheric aerosol samples by capillary electrophoresis after reversed pre‐electrophoresis

Abstract: This work presents the determination of low-molecular-mass (LMM) organic acids by CE after extraction with MeOH and preconcentration by evaporation. The interference arising from the simultaneous concentration of fast mobile anions (chloride, nitrate, and sulfate) at levels 200 times higher than those of LMM organic acids was reduced by the application of reversed pre-electrophoresis (RPE) as clean-up technique. This methodology allows for an effective elimination of high levels of fast mobile anions from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The use of a single ISTD for improving precision in conventional CE with hydrodynamic injection has been well investigated and shown to improve intracolumn RSDs to less than 1% . Two ISTDs have also been verified to correct for run‐to‐run variation with EKI methods in conventional CE , as well the application of an ISTD to correct for overlapping peaks . While ISTDs have been employed in some MCE applications , minimal investigation has been done on the effect of ISTDs on chip‐to‐chip variability.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a single ISTD for improving precision in conventional CE with hydrodynamic injection has been well investigated and shown to improve intracolumn RSDs to less than 1% . Two ISTDs have also been verified to correct for run‐to‐run variation with EKI methods in conventional CE , as well the application of an ISTD to correct for overlapping peaks . While ISTDs have been employed in some MCE applications , minimal investigation has been done on the effect of ISTDs on chip‐to‐chip variability.…”
Section: Introductionmentioning
confidence: 99%
“…14 Adding an internal standard (ISTD) to the sample is a standard technique used to improve run-to-run quantification in conventional capillary electrophoresis (CE) 5−7 and MCE. 8,9 In a recent paper, we demonstrated that adding an ISTD to the sample can be used not only to improve run-to-run quantification, but also improve chip-to-chip precision.…”
mentioning
confidence: 99%
“…To reduce residual error, it is common practice in CE and microchip CE to add an internal standard (ISTD) to the sample. In a recent paper, we verified the significance of chip‐to‐chip differences in quantification imprecision with a systematic investigation across six microfluidic chips, and further determined how well two ISTDs (Cs and Li) accounted for this error .…”
Section: Introductionmentioning
confidence: 99%